Tantangan Dan Peluang Bagi Mahasiswa Mahasiswi Universitas Victory Sorong Dalam Era Digital (Sebuah Analisis Sosial Budaya) - Natasya Virginia Leuwol; Gloria Irene Siahaya; Jevin Syella Ayawaila; Selviana Maer; Michelle Momot; Vira Sulfiana Salay (Journal Of Informatics And Busisnes, 2024)
The development of digital technology has had a significant impact on Victory University Sorong students. This study aims to analyze the challenges and opportunities faced by students in facing this digital era, with a focus on socio-cultural aspects. The research was conducted through surveys and in-depth interviews with a number of students, taking into account the use of technology, communication patterns, and changes in learning styles. The findings show that while technology offers greater access to information, challenges such as the digital divide and disruption to social interactions are also emerging. However, there are significant opportunities to improve educational accessibility.